Eksplorasi Penggunaan Tanaman Obat untuk Pengobatan Jerawat di Desa Bukian, Payangan-Bali - Ni Putu Sucitariningsih; Ida Ayu Manik Partha Sutema; Ni Putu Aryati Suryaningsih; I Putu Riska Ardinata (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2026)
Acne is a common dermatological condition affecting up to 85% of the global population, primarily triggered by hormonal fluctuations that increase sebum production and promote the proliferation of Cutibacterium acnes. The management of excessive sebum has become a crucial strategy in acne treatment, alongside conventional therapies such as antibiotics, including minocycline and doxycycline. Historically, prior to the development of synthetic pharmaceuticals, natural remedies played a significant role in acne treatment and continue to be widely used today, particularly in rural communities. Objective: This study aimed to explore the types of medicinal plants traditionally used as anti-acne treatments by the community of Bukian Payangan Village, Bali. Methods: This research employed a quantitative descriptive design. Sampling was conducted using the snowball sampling technique. Data were collected from 100 respondents using a structured checklist. Results: There were 13 types of anti-acne plants including Jackfruit, Fern, Lime, Teki Grass, Aloe Vera, Chinese Betel, Tomato, Moringa, Turmeric, Red Bean, Cucumber, Pepper, and Sandalwood, where Jackfruit (Artocarpus heterophyllus) had a Use Value the highest (0.44) came from the yard of the house (39%). The most widely used parts of the plant are leaves (64.30%) by processing, namely squeezed (54.95%) and used by pasting (87%) on acne-prone facial areas. The most felt benefits related to reducing oily skin. Conclusion: There are as many as 13 plants as anti-acne, with the dominance of use on the leaves and having the main effect of sebum control.